Know your remedies : pharmacy and culture in early modern China - Bian, He, 1984- (Princeton University Press, 2020)
"Traditional Chinese medicine has been practiced in various forms for more than a thousand years. Practitioners may heal patients with herbal remedies, acupuncture, massage, exercise, and modified diets. Even today, herbal medicines are of particular importance; Chinese pharmacies containing a vast array of remedies can be found in cities and towns the world over. This book is an interdisciplinary and cultural history of the concept of "pharmacy," both the drugs themselves and the trade in medicine, during the Ming and Qing dynasties of early modern China. This was a time of change for traditional Chinese medicine and for Chinese science as a whole. Many historians have argued that sixteenth-century China was a high point of scientific inquiry, followed by a period of intellectual decline. Though political and intellectual shifts led to a crisis of authority over pharmaceutical knowledge in the sixteenth through eighteenth centuries, Bian argues that this period of supposed intellectual decline was in fact characterized by numerous efforts to further refine and spread the pharmacological knowledge amassed in the Ming dynasty. She draws on a wide range of primary sources, but particularly through the study of bencao (pronounced "pen ts'ao"), a genre of encyclopaedic works, often called matteria medica or pharmacopoeia in the West, that collect information on medicinal substances. As the early modern Chinese Empire expanded and print culture became more widespread, the pursuit of medical remedies became a significant commercial enterprise. The author connects theory and practice of pharmacy during the Ming and Qing dynasties to broader developments in intellectual history, book culture, commerce, and taxation"--